Perencanaan Strategis DP3AKKB Provinsi Banten Dalam Pencegahan Kekerasan Terhadap Anak Studi Kasus Program PATBM - Peri Supriatna; Ipah Ema Jumiati; Ayuning Budiati (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2021)
This research discusses the DP3AKKB Strategic Planning (Office of Empowerment of Women, Child Protection, Family and Family Planning). Province of Banten In Prevention of Violence Against Children Study Cases PATBM Program. The aim of this research was to find out how DP3AKKB Strategic Planning in Banten Province in Prevention of Violence Against Children Study Program PATBM. This research uses a descriptive method with a qualitative approach. The Determination of informants uses purposive sampling techniques. Data collection techniques are observation, interview and documentation. The trustworthiness  of the data using triangulation of data sources and member checks associated with the theory of the Strategic Planning Process according to Michael Allison and Jude Keye, 2005. Data analysis techniques use Miles and Hubbermman. The results showed that the Strategic Planning of DP3AKKB (Office of Empowerment of Women, Child Protection, Population and Family Planning) is still not optimal. In strategic planning has obstacles such as in the Pre-preparation of proposals with facts out of sync, in assessing the external environment lacking coordination and synergy across sectors with DP3AKKB City, LPA District, District/ Village, human resources in the evaluation field are inadequate, there are still those who have not conducted PATBM training, the carrying capacity of service facilities and infrastructure is inadequate such as not having a Technical Service Unit, PATBM does not yet have a budget allocation from the local village. The necessity of synchronize violence prevention programs between Provinces and Regencies / Cities.